Active vision sensing and feedback control of back penetration for thin sheet aluminum alloy in pulsed MIG suspension welding. (May 2019) - Xiong, Jun; Zou, Shuangyang
Highlights: A computer vision sensing is designed for aluminum alloy weld pool detection. Image processing algorithms are proposed for back width monitoring. Step response and model simulation are conducted for controller optimization. Comparison tests between open and closed-loop control are carried out. Abstract: Consistent penetration control of thin sheet aluminum alloy in automatic pulsed metal inert gas (MIG) welding can help ensure its welding quality. In this research, a novel active vision sensing system consisting of a camera and an auxiliary light source has been designed for back penetration monitoring in pulsed MIG suspension welding for aluminum alloy, possessing the ability of intensifying weld seam features and anti-interference to arc lights. Corresponding image processing algorithms were developed to suppress noises and calculate back width of weld pool. Then a fuzzy controller was proposed to control back penetration of aluminum alloy in pulsed MIG suspension welding by means of adjusting the welding current. Butt welding and variable heat dissipation tests under constant welding current and closed-loop control demonstrated that the closed-loop controller can solve the lack of penetration issue during the welding process and can prevent increased back width when the heat dissipation conditions are deteriorated. Furthermore, the maximum deviation between the detected and given width can be controlled to be within ±0.5 mm in these tests, and mean square deviations were less than 0.32, which is acceptable for weld formation control.